2010
DOI: 10.1007/s00216-010-4171-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro phase I metabolism of the synthetic cannabimimetic JWH-018

Abstract: A potent synthetic cannabinoid receptor agonist, JHW-018, was recently detected as one of the most prominent active agents in abusively used incenses such as Spice and other herbal blends. The high pharmacological and addictive potency of JWH-018 highlights the importance of elucidating the metabolism of JWH-018, without which a meaningful insight into its pharmacokinetics and its toxicity would not be possible. In the present study, the cytochrome P450 phase I metabolites of JWH-018 were investigated, after i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
104
1
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(117 citation statements)
references
References 19 publications
6
104
1
6
Order By: Relevance
“…Many of these hydroxylated metabolites have been shown to be monohydroxy derivatives of the naphthalene, indole, or side-chain moieties (Sobolevsky et al, 2010) that are excreted in urine primarily as glucuronic acid conjugates (Sobolevsky et al, 2010;Wintermeyer et al, 2010;Moran et al, 2011), thus implicating the involvement of UGTs in this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these hydroxylated metabolites have been shown to be monohydroxy derivatives of the naphthalene, indole, or side-chain moieties (Sobolevsky et al, 2010) that are excreted in urine primarily as glucuronic acid conjugates (Sobolevsky et al, 2010;Wintermeyer et al, 2010;Moran et al, 2011), thus implicating the involvement of UGTs in this process.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas as many as 10 different K2-AAIs are reported to be present in various K2 preparations, the two commonly observed derivatives are JWH-018 and JWH-073 (Vardakou et al, 2010). There are indications that both Phase I and Phase II are involved in the metabolism of these two compounds in vivo (Sobolevsky et al, 2010;Wintermeyer et al, 2010;Moran et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Pentyl chain hydroxylation and further glucuronidation, carboxylation, and naphthalene dihydrodiol formation were detected for both (11,14 ). However, susceptibility to metabolism was different for indole (JWH-018) and indazole (THJ-018) rings.…”
Section: Thj-018 and Thj-2201 Metabolism Compared With Jwh-018 And Ammentioning
confidence: 99%
“…However, JWH-018 and AM-2201 metabolism have been intensively studied (12, 14 -16 ). JWH-018 undergoes monohydroxylation on the naphthalene, indole, and pentyl chain, as well as carboxylation (14,15 ). In contrast, AM-2201 primarily undergoes oxidative defluorination and subsequent carboxylation (12,16 ).…”
mentioning
confidence: 99%
“…Nevertheless, several analytical methods were developed to determine some of these new 812 psychoactive substances and/or their metabolites in either blood or urine (Moran et al, 2011;813 Grigoryev et al, 2011;Dresen et al, 2011;Teske et al, 2010;Wintermeyer et al, 2010;Beuck et 814 al., 2011;Kraemer et al, 2009;Sobolevsky, Prasolov, & Rodchenkov, 2010 proposed (Martin et al, 2012). The study reported that 67 real hair samples were analyzed -10 were 822 found positive, with mephedrone concentrations from 0.2 to 313.2 ng/mg; 8 of them were below 6 823 ng/mg.…”
mentioning
confidence: 99%